2021
DOI: 10.1029/2020jd033682
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and Evolution of the Antarctic Peninsula Föhn Wind‐Induced Melt Regime From 1979–2018

Abstract: Antarctic Peninsula (AP) surface melt has increased in the past half-century in response to anthropogenic increases in surface temperature (Barrand et al., 2013). Surface melt-induced firn air depletion and densification contribute to the hydrofracture process thought to have preceded the collapse of Larsen A and B ice shelves off the eastern coast of the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 42 publications
(89 reference statements)
4
36
0
1
Order By: Relevance
“…The hindcast results presented in this study build upon previous work that has attempted to quantify the patterns of surface melting on Larsen C (e.g. 2020;King et al, 2017;Turton et al, 2018;2020;Weisenekker et al, 2019;Kirchgaessner et al, 2019;Datta et al, 2019;Laffin et al, 2021). These results advance our understanding by using a non-hydrostatic RCM at sufficiently high resolution to capture foehn winds, which are demonstrably important for determining surface melt.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The hindcast results presented in this study build upon previous work that has attempted to quantify the patterns of surface melting on Larsen C (e.g. 2020;King et al, 2017;Turton et al, 2018;2020;Weisenekker et al, 2019;Kirchgaessner et al, 2019;Datta et al, 2019;Laffin et al, 2021). These results advance our understanding by using a non-hydrostatic RCM at sufficiently high resolution to capture foehn winds, which are demonstrably important for determining surface melt.…”
Section: Discussionsupporting
confidence: 71%
“…However, despite their importance for inducing melt over Larsen C, a comprehensive long-term estimate of how frequently foehn events occur and their associated impacts on atmospheric conditions and the SEB over the Larsen C ice shelf has not yet been made. Several estimates of foehn frequency have been made using Automatic Weather Stations (AWSs) on the ice shelf (Turton et al, 2018;2020;Weisenekker et al, 2019;Laffin et al, 2021) or over relatively short time periods of a year or less (King et al, 2017;Kirchgaessner et al, 2019;Elvidge et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Según Cook et al (2016), cerca de 90% de los glaciares del OPA se está reduciendo, así como la extensión del hielo marino y su duración media, llegando a unos 90 días (Stammerjohn et al, 2012). En Laffin et al (2021) investigando la influencia de los vientos cálidos y secos de föhn en el derretimiento de la superficie de plataformas de hielo en la península Antártica para 1979-2018, encontraron que las tendencias y la evolución de la fusión a largo plazo inducida por föhn son atribuibles a cambios estacionales. Durante los últimos 20 años, la mayor ocurrencia de föhn se presenta en el verano, con una disminución en otoño, invierno y principios de primavera, lo que concuerda con las tendencias decadales de CHM del presente estudio, sobre todo para los puntos al sur y norte del estrecho de Gerlache.…”
Section: Discussionunclassified
“…Las diferencias duration, reaching approximately 90 days (Stammerjohn et al, 2012). Laffin et al (2021), conducting research on the influence of the warm and dry föhn winds on the melting of the surface of ice platforms in the Antarctic peninsula for 1979-2018, found that the trends and evolution of longterm fusion induced by föhn can be attributed to seasonal changes; During the last 20 years, the highest occurrence of föhn happens in summer, with a decrease in autumn, winter and early spring, which matches the SIC decadal trends shown in this study, especially for the points located at the south and north of the Gerlache strait.…”
Section: Conclusionesmentioning
confidence: 99%
“…Laffin et al. (2021) examine the impact of foehn winds on melting during 1979–2018 using machine learning and the RACMO2.3 model, and Turton et al. (2020) combine observations and model output from AMPS (Antarctic Mesoscale Prediction System) to explore seasonal patterns in foehn‐driven surface melt.…”
Section: Introductionmentioning
confidence: 99%